2007
DOI: 10.1016/j.cep.2007.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid synthesis in a microstructured reactor for process intensification

Abstract: Ionic liquids (IL) are the focus of growing interest over the last few years due to their low vapour pressure being beneficial for replacing common organic solvents with high vapour pressure. IL synthesised via alkylation are produced in batch or semi-batch stirred tank reactors. The reaction is highly exothermic and the kinetics was shown to be fast. The heat management during the reactor operation is a crucial point leading to high quality IL product and avoiding thermal runaway. This study reports the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 11 publications
2
58
0
1
Order By: Relevance
“…Löb et al (2007) demonstrated that even a dropwise addition of alkylating agent to the bulky amine in a labscale batch vessel gave raise of a local temperature of the mixture up to 150 ºC. The chemical entities of the coloring matter are still not clear, but several authors agree that imidazolium species participate in the creation of colored compound, either by its polymerization or decomposing at high temperature (Renken et al, 2007). Therefore, in order to improve the purity of ionic liquids, an efficient removal of released reaction heat is crucial.…”
Section: Problems Associated With the Preparation Of Ionic Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…Löb et al (2007) demonstrated that even a dropwise addition of alkylating agent to the bulky amine in a labscale batch vessel gave raise of a local temperature of the mixture up to 150 ºC. The chemical entities of the coloring matter are still not clear, but several authors agree that imidazolium species participate in the creation of colored compound, either by its polymerization or decomposing at high temperature (Renken et al, 2007). Therefore, in order to improve the purity of ionic liquids, an efficient removal of released reaction heat is crucial.…”
Section: Problems Associated With the Preparation Of Ionic Liquidmentioning
confidence: 99%
“…Obtained ionic liquids were of high quality and, in certain process conditions, reaction times were reduced down to minutes as opposed to conventional batch systems in which reaction time was measured in hours, even days (Waterkamp et al, 2007;Renken et al, 2007). Waterkamp et al (2007) presented a way to intensify the solvent-free synthesis of 1-butyl-3-methylimidazolium bromide ([BMIM]Br) from 1-methylimidazole (MeIm) and 1-bromobutane (BrBu), using a continuously operating microreactor system consisted of a vortex-type micromixer (0.45 mm channel width) followed by series of three tubes with increasing inner diameter (2-6 mm).…”
Section: Benefits Of the Ionic Liquid Synthesis Within Microfluidic Dmentioning
confidence: 99%
“…The model reaction used for the simulation has to be 1) quasi-instantaneous with a characteristic reaction time below 1 second and 2) highly exothermic. For this reason, the synthesis of the ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate at higher temperature was chosen, whose kinetics is well described in literature [12][13][14]. The adiabatic temperature rise of the reaction, i.e., the temperature rise obtained in absence of cooling, is ∆T ad = 166°C.…”
Section: Modeling Of a Multi-injection Microreactormentioning
confidence: 99%
“…The synthesis of the ionic liquid, 1,3-methylmethylimidazolium dimethyl phosphate, was based on previously described methods [14][15][16]. The IL structure characterization was verified by 1 H NMR (JNE-ECS-400MHz, JEOL, Japan).…”
Section: Materials Preparationmentioning
confidence: 99%